The prevalence of comorbidity in rheumatoid arthritis: a systematic review and meta-analysis. (2nd May 2022) - Hill, James; Harrison, Joanna; Christian, Danielle; Reed, Janet; Clegg, Andrew; Duffield, Stephen J; Goodson, Nicola; Marson, Tony
Abstract : This systematic review and meta-analysis estimates the prevalence of common comorbid health disorders in adults with rheumatoid arthritis (RA). A multi-database search strategy was undertaken. Screening, data extraction and quality assessment were carried out by two independent reviewers. A meta-analysis and meta-regression were used to generate a pooled prevalence estimate and identify relevant moderators. After study selection, 33 studies (74633 participants) were included in the meta-analysis. Some 31 studies were judged to be of low risk of bias, and two studies were judged to be at moderate risk of bias. The three most common comorbidities in RA were anxiety disorders (62.1%, 95% Cl: 43.6%; 80.6%), hypertension (37.7%, 95% Cl: 29.2%; 46.2%) and depression (32.1%, 95% Cl: 21.6%; 42.7%). There was substantial statistically significant heterogeneity for all comorbidities (I2 ≥77%). Meta-regression identified that the covariate of mean age (unit increase) had a statistically significant effect on the prevalence of hypertension (+2.3%, 95% Cl: 0.4%; 4.2%), depression (−0.5%, 95% Cl: −0.6%; −0.4%) and cancer (0.5%, 95% Cl: 0.2%; 0.8%) in adults with RA. A country's income was identified to have a statistically significant effect on the prevalence of depression, with low-to moderate-income countries having 40% (95% Cl: 14.0%; 66.6%) higher prevalence than high-income countries. No studies consider health inequalities. It is concluded that comorbidities are prevalent among people with RA, particularly those associated with mental health and circulatory conditions. Provision of health services should reflect the importance of such multimorbidity and the consequences for quality and length of life.